Perlindungan Hukum bagi Konsumen atas Kelangkaan Minyak Goreng Ditinjau dari Undang-Undang Nomor 8 Tahun 1999 tentang Perlindungan Konsumen - Purwanti, Maya Novira; Hariri, Achmad (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2022)
This journal focuses on the position of consumers when there is a shortage of cooking oil as it is today, where cooking oil is one of the 9 staple ingredients that must be guaranteed availability. By using Law No. 8 of 1999 concerning Consumer Protection as the main reference material. This research will review about consumer legal protection to meet basic needs and legal remedies for consumers who experience a shortage of cooking oil products. The research method used is normative with a statute approach, using the law as a key instrument. The result is that based on the applicable law, the community can get legal protection for their right to obtain goods, in this case cooking oil, if in certain circumstances there is a scarcity or unavailability of an item or service. The community can even complain about their problems to the appointed agency and can file a lawsuit against the parties concerned for the violation of their rights. Socialization and awareness to the public on consumer protection is absolutely necessary to increase awareness, ability and empowerment of consumer rights.